A 3D Cu-Naphthalene-Phosphonate Metal-Organic Framework with Ultra-High Electrical Conductivity - Peeples, Craig A.; Kober, Delf; Schmitt, Franz-Josef; Tholen, Patrik; Siemensmeyer, Konrad; Halldorson, Quinn; Cosut, Bunyemin (Wiley-V C H Verlag Gmbh, 2021)
A conductive phosphonate metal-organic framework (MOF), [{Cu(H2O)}(2,6-NDPA)(0.5)] (NDPA = naphthalenediphosphonic acid), which contains a 2D inorganic building unit (IBU) comprised of a continuous edge-sharing sheet of copper phosphonate polyhedra is reported. The 2D IBUs are connected to each other via polyaromatic 2,6-NDPA's, forming a 3D pillared-layered MOF structure. This MOF, known as TUB40, has a narrow band gap of 1.42 eV, a record high average electrical conductance of 2 x 10(2)S m(-1)at room temperature based on single-crystal conductivity measurements, and an electrical conductance of 142 S m(-1)based on a pellet measurement. Density functional theory (DFT) calculations reveal that the conductivity is due to an excitation from the highest occupied molecular orbital on the naphthalene-building unit to the lowest unoccupied molecular orbital on the copper atoms. Temperature-dependent magnetization measurements show that the copper atoms are antiferromagnetically coupled at very low temperatures, which is also confirmed by the DFT calculations. Due to its high conductance and thermal/chemical stability, TUB40 may prove useful as an electrode material in supercapacitors.
Keywords: electrically conductive MOFs; magnetic MOFs; phosphonate MOFs; semiconductors; supercapacitors